Improve the Forming Ability of Al-Based Metallic Glass Under Ultrasonic Vibration at Room Temperature - Liang, Xiong; Fan, Caitao; Fu, Jianan; Liu, Zehang; Zhang, Zhenxuan; Ren, Shuai; Ruan, Wenqing; Shi, Hongyan (Frontiers in Materials, 2021)
In this work, a rapid and controllable ultrasonic vibration (UV) method for forming Al-based metallic glass (MG) at room temperature is proposed. This method can dramatically improve the plasticity and forming ability of Al-based MGs, which are virtually brittle at room temperature and have almost no supercooled liquid region (SLR) at high temperatures. Under UV, Al-based MGs exhibited obvious plastic flow, with a maximum plasticity of up to 58% and an average plasticity of up to 43%. It is worth mentioning that no crystalline peaks were found on the X-ray diffraction patterns after deformation under UV, and the mechanical properties remained the same as the primary sample. The present results provide a new approach for the deformation and forming of Al-based MGs, which can significantly broaden their applications.